Osteoclast biology in the single-cell era - Masayuki Tsukasaki; Hiroshi Takayanagi (BMC, 2022)
Abstract Osteoclasts, the only cells that can resorb bone, play a central role in bone homeostasis as well as bone damage under pathological conditions such as osteoporosis, arthritis, periodontitis, and bone metastasis. Recent studies using single-cell technologies have uncovered the regulatory mechanisms underlying osteoclastogenesis at unprecedented resolution and shed light on the possibility that there is heterogeneity in the origin, function, and fate of osteoclast-lineage cells. Here, we discuss the current advances and emerging concepts in osteoclast biology.